2019
DOI: 10.3389/fonc.2019.00656
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Tumor-Associated Macrophage Content in Head and Neck Squamous Cell Carcinoma: A Meta-Analysis

Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) exists within a microenvironment rich in immune cells. Macrophages are particularly abundant in and around tumor tissue, and have been implicated in the growth, malignancy, and persistence of HNSCC ( 1 ). However, current literature reports variable degrees of association between the density of tumor-associated macrophages (TAMs) and clinicopathologic markers of disease ( 2 , 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 68 publications
4
71
0
1
Order By: Relevance
“…As we know this is the first publication covering such a homogeneous group of patients with a comparable number of HPV-positive and HPV-negative cases and one of the few in which the HPV double-detection algorithm was used. Most of the publications in which the intensity of macrophage infiltration within head and neck tumours was analysed concerned locations in the oral cavity [30] or other locations outside the oropharynx [31], where HR-HPV status was unknown. Due to the low frequency of HR-HPV infections in the 2.5-4% range in these anatomical sites, it can be assumed that the results presented in them relate mainly to the HPV-negative population [32][33][34].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we know this is the first publication covering such a homogeneous group of patients with a comparable number of HPV-positive and HPV-negative cases and one of the few in which the HPV double-detection algorithm was used. Most of the publications in which the intensity of macrophage infiltration within head and neck tumours was analysed concerned locations in the oral cavity [30] or other locations outside the oropharynx [31], where HR-HPV status was unknown. Due to the low frequency of HR-HPV infections in the 2.5-4% range in these anatomical sites, it can be assumed that the results presented in them relate mainly to the HPV-negative population [32][33][34].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Subsequently, in all the examined cases, the presence and types of HR-HPV DNA in the tumour cells were confirmed using commercially available test, Sacace HPV Genotypes 14 Real-TM (Sacace Biotechnologies Srl, Italy), which is a real-time PCR Kit for quantitative detection and genotyping of HR-HPV (16,18,31,33,35,39,45, 51, 52, 56, 58, 59 and 68). The first step of the procedure was to isolate the genomic DNA from all tumour tissue samples by using Mag Core Genomic DNA FFPE One-step Kit and MagCore Nucleic Acids Automatic Extractor HF16-Plus (RBC Bioscience Corp. Taiwan).…”
Section: Hr-hpv Status Assessmentmentioning
confidence: 99%
“…Visual details on protein distribution and localization can be procured without the need to destroy the histologic architecture of a tissue (48). Accordingly, studies focusing on TAM characterization in solid clinical samples often adopt immunohistochemistry in their methodologies till date (8,49,50). In contrast, methods such as flow cytometry and gene expression are performed in vitro and could not reflect the complexity of immune responses observed in vivo (51,52).…”
Section: Evaluation Of M1 and M2 Polarization In Tissue Section: Techmentioning
confidence: 99%
“…Our results show that the high level of Tregs infiltration is significantly associated with the low risk score, which is associated with favorable prognosis. Macrophages that infiltrate into the tumor microenvironment may facilitate tumor growth, angiogenesis, invasion, and metastasis, and are associated with poor prognosis in HNSCC [50]. Our study indicated that they are positively associated with risk score and an increase in M0 macrophages portends a poor prognosis.…”
Section: Genetic Alterations and Gsea Analysis In The High-risk Groupsmentioning
confidence: 54%